Hubungan Pengetahuan Ibu, Pendidikan dan Sosial Ekonomi Dengan Status Gizi Pada Balita di Puskesmas Bendahara Tahun 2019 - Nova Radiani Br Hsb; Irma Sari (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Nutritional status of infants is influenced by many factors the direct factors and indirect factors. Initial survey conducted by researchers at the Health Center IHC Treasurer at the time of the visit, it was found through interviews and observations Health Card (KMS) found 2 toddlers (40%) with the nutritional status of the Lower Red Line (BGM) and the mother's lack of knowledge about nutrition while 3 people (60%) with 2 BGM not knowledgeable enough mothers and 1 mother with good knowledge. Research is research that researchers use to obtain Relations Analytical Knowledge Capital, Education and Social Economy With Nutritional Status In Toddlers In Work Area Health Center Tamiang District Treasurer in 2019. Population in this study were all mothers with children under five that exist in the working area Treasure of the puskesmas 2019 when the study lasted a total sample of 43 people. The sample selection is done by accidental sampling. The results of this study can be seen in the majority of the nutritional status of children under five (30.2%), compared with BGM nutritional status of 25.6%, means that there is a relationship between knowledge, education and socioeconomic status of the mother on nutrition in infants. Thus better the knowledge, education and socio-economic one person, the better the nutritional status toddler. This study is expected in an effort to increase knowledge and education in an effort to improve nutrition toddler mom - mother to visit an active role - such as health centers posyandu.Keywords: Nutritional Status, Toddlers, Knowledge, Education, Socioeconomic.